Automatically Generated Smartphone Data in Young Patients With Newly Diagnosed Bipolar Disorder and Healthy Controls - Melbye, Sigurd; Stanislaus, Sharleny; Vinberg, Maj; Frost, Mads; Bardram, Jakob Eyvind; Kessing, Lars Vedel; Faurholt-Jepsen, Maria (Frontiers in Psychiatry, 2021)
Background Smartphones may facilitate continuous and fine-grained monitoring of behavioral activities via automatically generated data and could prove to be especially valuable in monitoring illness activity in young patients with bipolar disorder (BD), who often present with rapid changes in mood and related symptoms. The present pilot study aimed in young patients with newly diagnosed BD and healthy controls (HC)to 1) validate automatically generated smartphone data reflecting physical and social activity and phone usage against validated clinical rating scales and questionnaires 2) investigate differences in automatically generated smartphone data between young patients with newly diagnosed BD and HC; 3) investigate associations between automatically generated smartphone data and smartphone-based self-monitored mood and activity in young patients with newly diagnosed BD. Methods A total of 40 young patients with newly diagnosed BD and 21 HC aged 15 to 25 years provided daily automatically generated smartphone data for three to 779 days (median [IQR]= 140 [11.5-268.5]), in addition to daily smartphone-based self-monitoring of activity and mood. All participants were assessed with clinical rating scales. Results 1) The number of outgoing phone calls was positively associated with scores on the Young Mania Rating Scale and subitems concerning activity and speech. The number of missed calls (p= 0.015) and the number of outgoing text messages (p= 0.017) were positively associated with the level of psychomotor agitation according to the Hamilton Depression Rating scale subitem 9. 2) Young patients with newly diagnosed BD had higher number of incoming calls compared with HC (BD: Mean= 1.419, 95% CI: 1.162; 1.677, HC: Mean= 0.972, 95% CI: 0.637; 1.308, p=0.043) and lower self-monitored mood and activity (ps<0.001). 3). Smartphone-based self-monitored mood and activity were positively associated with step counts and the number of outgoing calls, respectively (ps<0.001). Conclusion Automatically generated data on physical and social activity and phone usage seems to reflect symptoms. These data differ between young patients with newly diagnosed BD and HC and reflect changes in illness activity in young patients with BD. Automatically generated smartphone-based data could be a useful clinical tool in diagnosing and monitoring illness activity young patients with BD.